Comparative and correlation analysis of experimental work for development of university teacher's knowledge management skills - Diana A. Kalmykova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper considers the problem of the inconsistency of the traditional educational process of higher education with changes in the socio-economic environment at the present stage of development of society. The conditions that are necessary today for training students with multidisciplinary thinking oblige the teacher to act as a consultant, coach, mentor and manager-organizer of the educational process, which has now become identical to the knowledge management process. Changing the role of the teaching staff of the educational organization of higher education actualizes the task of development of university teacher's knowledge management skills. The article presents the results of comparative and correlation analyzes of experimental work on development of university teacher’s knowledge management skills, considered as an integrative property of a person, combining value-motivational, instrumental-digital, scientific-research, evaluative-analytical, interactive-communication and academic and business components. The author proposed indicators of the selected components in the readiness structure, described their development and determined the dominant indicators of each component as a result of establishing and formative experiments. The materials of the experimental work presented in the article are aimed at identifying and enhancing both the relationships between the components of development and the relationships between the dominant indicators of structural elements. The results obtained indicate the development of all components in the readiness structure by means of additional professional educational programs. The analysis allows us to talk about the possibility of forming the components of the university teacher’s development for knowledge management due to the compensatory properties of indicators of the elements of its structure.